Interplay of substrate polymorphism and conformational plasticity of Plasmodium tyrosyl-tRNA synthetase. (December 2021) - Datt, Manish
Abstract: Aminoacyl-tRNA synthetases are an indispensable component of ribosomal protein translational machinery and Plasmodium Tyrosyl-tRNA synthetase ( Pf TyrRS) is a validated drug target. This manuscript illustrates the dynamic conformational landscape of Pf TyrRS in the context of substrate binding. Molecular dynamics simulations of Pf TyrRS in the presence and absence of ligand show conformational heterogeneity for both the protein and the bound ligand. Diverse conformations for the evolutionarily conserved ATP binding motif (KMSKS) have been observed in both apo- and holo Pf TyrRS. Further, the presented attributes of the tyrosyl-adenylate conformational sub-states in situ along with their implications on the strength of intermolecular interactions would be a pertinent benchmark for molecular design studies. In addition, an analysis of the ligand hydration pattern foregrounds the structurally conserved water-mediated inter-molecular interactions. The quantitative assessment of the conformational landscape, based on the fluctuations of the distance between the ligand binding pockets, of apo- Pf TyrRS and holo- Pf TyrRS highlights the nature of diversity in conformational sampling for the two cases. Evidently, the holo- Pf TyrRS adopts a rather compact conformation compared to the apo- Pf TyrRS. An intriguing asymmetry in the dynamics of the two monomers is contextualized with the functional asymmetry of the symmetrically dimeric Pf TyrRS. Importantly, the network of non-bonded contacts in the apo- and holo- simulated ensembles has been analyzed. The graph-theoretic analysis-based novel insights concerning the nature of information flow as a function of ligation state would prove valuable in understanding Pf TyrRS functions. The results presented here contend that understanding allostery in Pf TyrRS is essential to astutely design structure-based inhibitors. Graphical Abstract: ga1 Highlights: The simulated Pf TyrRS ensemble illustrates its conformational plasticity in the context of substrate binding. Polymorphic states for the bound substrate were observed. Pf TyrRS conformational sub-states can guide rational inhibitor design.